Switchable single- and dual-wavelength thulium/holmium co-doped fiber laser with single-longitudinal mode output. (3rd November 2021) - Han, Wenguo; Yan, Fengping; Feng, Ting; Yang, Dandan; Qin, Qi; Cheng, Dan; Li, Ting; Bai, Zhuoya; Suo, Yuping; Zhou, Hong
Abstract: A single-longitudinal-mode ring thulium/holmium co-doped fiber laser (THDFL) possessing the switchable single- and dual-wavelength outputs is proposed with two subring cavities and two polarization-maintaining fiber Bragg gratings. The switching operation is realized by tuning the pump power and polarization controller together. When the THDFL working at single-wavelength output state, the optical signal-to-noise ratio (OSNR) is ∼51 dB, and the maximum power and wavelength fluctuation within 1 h are 0.804 dB and 0.04 nm, respectively. Using the phase noise analysis-based linewidth measurement system, the linewidth is measured to be 0.16 MHz with a measuring time of 0.002 s. When the THDFL working at dual-wavelength output state, the OSNR is ∼55 dB, and the maximum power and wavelength fluctuation within 1 h are 0.802 dB and 0.05 nm, respectively. The proposed THDFL may find wide applications in microwave photonics generation and optical fiber laser sensor.